A case of neonatal gastric teratoma complicated with occult gastrointestinal hemorrhage misdiagnosed as lymphangioma - Bin De Li; Kexiang Wei (The Turkish Journal of Pediatrics)
Background. Gastric teratoma is a rare neoplasm, particularly in neonates, and usually presents as a palpable abdominal mass. However, severe occult gastrointestinal bleeding is uncommon and often misdiagnosed. Imaging studies are crucial for the preoperative diagnosis of neonatal teratoma, but definitive diagnosis relies on pathological examination.